2014
DOI: 10.4319/lo.2014.59.2.0311
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐aerobic bacterial methane oxidation in the chemocline and anoxic water column of deep south‐Alpine Lake Lugano (Switzerland)

Abstract: We measured seasonal variations in the vertical distribution of methane concentration, methane oxidation rates, and lipid biomarkers in the northern basin of Lake Lugano. Methane consumption below the oxic-anoxic interface co-occurred with concentration maxima of 13 C-depleted C 16 fatty acid biomarkers (with d 13 C values as low as 270%) in the anoxic water column, as well as characteristic d 13 C CH 4 profiles. We argue that the conspicuous methane concentration gradients are primarily driven by (micro-)aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
214
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 138 publications
(236 citation statements)
references
References 64 publications
22
214
0
Order By: Relevance
“…As NO 3 -, which is also rapidly reduced to NO 2 -in anoxic sediments, did not enhance CH 4 oxidation, it can be suggested that the CH 2 F 2 -induced inhibition of the potential CH 4 oxidation was not due to the inhibition of NO 2 -using NC 10 bacteria, but rather due to the inhibition of aerobic MOBs. Indeed, a risk of minor O 2 contamination from the substrate/tracer injection or due to diffusion from the rubber septa or silicon sampling ports during incubations, which could induce microaerobic CH 4 oxidation, has been acknowledged in previous incubation studies of anoxic freshwater samples (Blees et al 2014;á Norði and Thamdrup 2014). It is, therefore, possible that the diffusion of trace amounts of O 2 from the septa during the incubation period could not be fully prevented in this study, either.…”
Section: Microbial Community Structurementioning
confidence: 39%
“…As NO 3 -, which is also rapidly reduced to NO 2 -in anoxic sediments, did not enhance CH 4 oxidation, it can be suggested that the CH 2 F 2 -induced inhibition of the potential CH 4 oxidation was not due to the inhibition of NO 2 -using NC 10 bacteria, but rather due to the inhibition of aerobic MOBs. Indeed, a risk of minor O 2 contamination from the substrate/tracer injection or due to diffusion from the rubber septa or silicon sampling ports during incubations, which could induce microaerobic CH 4 oxidation, has been acknowledged in previous incubation studies of anoxic freshwater samples (Blees et al 2014;á Norði and Thamdrup 2014). It is, therefore, possible that the diffusion of trace amounts of O 2 from the septa during the incubation period could not be fully prevented in this study, either.…”
Section: Microbial Community Structurementioning
confidence: 39%
“…Recent research demonstrates that microaerobic methanotrophy is of significant ecological importance (Blees et al, 2014;Bar-Or et al, 2015;Chistoserdova, 2015;Hernandez et al, 2015). Most of these studies refer to lake sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic oxidation of methane is classically observed at the oxicanoxic interface of the water column (Rudd et al 1976;Schubert et al 2010), which forms in eutrophic lakes either during the stratification period in holomictic lakes or is permanently present in meromictic lakes. Recent studies indicate that aerobic methane oxidation occurs not only at and above the oxic-anoxic interface, but also in apparently anoxic zones which are virtually oxygen free (Blees et al 2014;Milucka et al 2015). We refer to zones with oxygen concentrations below the detection limit of the trace oxygen sensors (20 nmol l -1 ) as virtually anoxic zones.…”
Section: Introductionmentioning
confidence: 99%